Museu do cotidiano: um gabinete de histórias - Isabela Vecci Abijaude (2019)
This dissertation seeks to contribute to the institutionalization of the private collection of objects of Antônio Carlos Figueiredo, located in Belo Horizonte, Minas Gerais, in order to make it accessible to the public. This collection consists of thousands of objects of daily use and stories related to objects, grouped by the collector for 30 years in various spaces, the main one being a large store of 350m². The research initially sought to identify the collector and his procedures for collecting the objects that constituted the collection and to establish a dialogue with a European social phenomenon of the sixteenth and seventeenth centuries, called the cabinet of curiosities. Next, it seeks to situate it in the context of studies on material culture, in the aspects of contemporary museology and to identify the strategies of organization of the collection in the space where it is currently, denominated by the collector of Museu da Cotidiano. Finally, it will establish guiding concepts for the production of a museological plan with the objective of assisting in its future institutionalization.